Determining Company Financial Performance: Analysis of Liquidity, Leverage, and Company Size (Literature Review on Financial Management) - Idrus, Mohammad Reihan; Alfasyah , Muhammad Afga (Universitas Dehasen Bengkulu, 2025)
Previous or relevant research is crucial in research or scientific articles because it provides a basis for strengthening theories and explaining the phenomenon of relationships or influences between various existing variables. This article conducts a study on the determination of a company's financial performance by analyzing factors such as liquidity, leverage, and company size. Through this literature research, several important findings were found: first, liquidity is proven to have a significant effect on a company's financial performance; second, leverage also has an impact on a company's financial performance; and third, company size does not show a significant effect on a company's financial performance. Thus, these results provide deeper insight into the factors that influence a company's financial performance, although company size does not seem to play a major role as previously thought. Further analysis is needed to further explore why company size does not show a significant effect